2015
DOI: 10.1007/s11051-015-3140-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon nanotubes upon emissions from cutting and sanding carbon fiber-epoxy composites

Abstract: Carbon nanotubes (CNTs) are being incorporated into structural composites to enhance material strength. During fabrication or repair activities, machining nanocomposites may release CNTs into the workplace air. An experimental study was conducted to evaluate the emissions generated by cutting and sanding on three types of epoxy-composite panels: Panel A containing graphite fibers, Panel B containing graphite fibers and carbon-based mat, and Panel C containing graphite fibers, carbon-based mat, and multi-walled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Bello et al showed that the use of wet suppression techniques during sawing of nanocomposites reduced exposures down to background levels (Bello et al 2009). A recent study has also shown that the ventilated enclosure built to contain a power sawing machine efficiently captured the dust generated by cutting and sanding nanocomposite panels (Heitbrink and Lo 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Bello et al showed that the use of wet suppression techniques during sawing of nanocomposites reduced exposures down to background levels (Bello et al 2009). A recent study has also shown that the ventilated enclosure built to contain a power sawing machine efficiently captured the dust generated by cutting and sanding nanocomposite panels (Heitbrink and Lo 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Information regarding CNTs emissions in working environments is still limited (Methner et al 2010; Heitbrink and Lo 2015; Heitbrink et al 2015). The goal of this study is to assess nanomaterial emissions from product development activities in a laboratory and contribute additional understanding about potential CNT exposure and effective control measures.…”
Section: Introductionmentioning
confidence: 99%
“…One paper on an international survey regarding occupational health and safety programs, engineering controls and PPE, did not contain data on the concentrations of airborne MNMs particles [13] and could not be used for the calculation of PFs. The remaining 14 papers reported on: enclosure systems (down flow clean rooms with ventilated enclosure hood); ventilation (LEV, enclosure type LEV with proper face velocity, process ventilation, biosafety cabinets); specialized ventilation systems (thermal displacement ventilation); and segregation sources (reactor cabinets) [7][8][9][10][11][12][14][15][16][17][18][19][20][21].…”
Section: Effects Of Enclosure and Ventilationmentioning
confidence: 99%
“…Based on the scores of the risk of bias in Table 2, we excluded 3 papers because of low scores of the risk of bias, in particular the score of RB1 [9,15,20]. The 11 papers reported 27 cases for which we could obtain the PF eng [7, 8, 10-12, 14, 16-19, 21].…”
Section: Effects Of Enclosure and Ventilationmentioning
confidence: 99%